The Importance of Infrastructures in the LDC’s Economic Sustainable Development - Ciminello, Romeo (European Journal of Sustainable Development, 2019)
Infrastructures are crucial for sustainable growth and inclusive development of Less Developed Countries. The problem in hypothesis is the African infrastructure gap, that neither governments nor civil society organizations seems to want to face promoting investments in tangible programs that take into consideration such kinds of important elements aimed to an equal durable and sustainable improvement. The paper starts with a description of recent initiatives to scale up infrastructure investment in Africa. The methodology follows a scheme of hypothesis, observations experiences and data collection from ADB and others Institutions. This research tries to let understand what is the connection between development and infrastructures for human being. The paper then uses insights from the literature on informed versus arm’s length debt to discuss the structure of infrastructure financing. The economic growth and its goal, outlines the difference between structures and infrastructures. The main effort is how to give a weight to these latter in order to measure the empowerment of people that pass through their standard of living based on a system of strategic priorities centered on infrastructure package investments. Understanding the importance of infrastructures helps to satisfy needs and implement services that even if deemed not essential and substantial, are anyway most important to the growth of personal and social conditions. In this context the analysis is made on the difference between economic growth and development grounded on structure and infrastructure. The effort is to try to identify indicators able to evidence the contribution ratio of infrastructures to the development, how this can be measured and how they work in the different fields. The conclusion and implications are that to yield such potential global benefits, Africa’s industrialization would have to be underpinned by a robust infrastructure financing program. This requires a global finance pact among advanced and developing countries, a shift in strategic approaches, and new models of financing. Keywords: Africa, Infrastructure Finance, Economic growth, Development Banks, Integral development economy, Long-term Investors, Development indicators, Economy of Francesco, Lonergan’s new economic vision